Land investments and human rights: how home countries can do more - Kaitlin Y. Cordes; Anna Bulman (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
The current failure of host governments and international law to protect human rights in the context of land-based investments highlights the need to employ other mechanisms. This Perspective discusses home country measures as one strategy for encouraging more rights-supportive outward investment in agricultural and forestry projects.
Keywords: 330